It's not me I swear! [videorecording (DVD)] - Falardeau, Philippe; L'Écuyer, Antoine; Clément, Suzanne; Brière, Daniel; Faucher, Catherine; Maillé, Gabriel ([Publisher not identified], 2014)
Leon is not like most ten-year olds. This innocent-looking boy with an overly fertile imagination is a young hellion, a consummate liar and thief well versed in breaking and entering his neighbors' homes and running away from his own. When his mom decides to pack up and leave for Greece, Leon does so much to keep her there.